Model Based Reverse Engineering With Restructuring Algorithm (International Journal of Scientific Research and Management (IJSRM), 2015)
GUI testing represents a significant amount of the overall testing efforts. Performing software testing through GUI in order to find defects in the application. In GUI it is more difficult than testing the application through its API because it requires additional programming effort to simulate user actions to observe the output produced and to check its correctness. The incorrect behavior of Graphical User Interfaces can compromise the effective use of the overall software application. One way to discover defects and increase the quality of GUIs is through testing. Test cases can be created manually or produced automatically from a model of the GUI. The size and complexity of GUIs makes it unpractical to do extensive manual testing. The GUI is exercised by a combination of manual and automatic exploration, and information about its structure and some of its behavior is automatically extracted, resulting in an incomplete GUI model.